Case of clinical canine leptospirosis in Uganda. Issue 4 (14th November 2017) - Alinaitwe, Lordrick; Kakooza, Steven; Eneku, Wilfred; Dreyfus, Anou; Rodriguez‐Campos, Sabrina
Abstract : In this report, we present the first confirmed case of clinical leptospirosis in a dog in Uganda. A five‐year‐old entire male German shepherd dog from a kennel of 25 guard dogs was admitted to the animal clinic and presented hypothermia, lethargy and jaundice of the mucous membranes. The body temperature remained low during the three days post admission until death. The postmortem examination and histological findings led to suspicion of acute leptospirosis. The diagnosis was confirmed by demonstration of pathogenic Leptospira spp DNA in homogenates of the kidney, liver and lungs by real‐time PCR. This case highlights that accurate diagnostic methods are needed to clarify if clinical leptospirosis is to date underestimated in Uganda and if it has an impact on public health. Awareness should be raised among veterinarians to consider leptospirosis more often as a differential diagnosis as a consequence of the non‐specific signs observed in the presented case.